Efektivitas Teknik Pernapasan Lamaze dalam Menurunkan Kecemasan dan Depresi pada Ibu Bersalin Primigravida - Rochmayanti, Shinta Nur; Kwarta, Cityta Putri; Imeldawati, Rakhmalia; Widiyasari, Eny; Nuraenayatin, Nina; Pratiwi, Dessy; Nafiata, Ikrimah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Childbirth is a process involving hormonal changes, emotional stress, and significant physical challenges. One notable factor is the emotional stress that can induce anxiety and depression, particularly in primigravid mothers. Some efforts are needed to address this problem, one them is the use of the Lamaze breathing technique. This study aims to determine the effectiveness of the Lamaze breathing technique in reducing labor pain, thereby impacting maternal anxiety and depression. The study employed a quasi-experimental design with a pre-test and post-test approach. The study sample consisted of 40 primigravid mothers, randomly assigned to either the intervention group (n=20), which received Lamaze breathing technique training, or the control group (n=20), which received standard midwifery care. The results of the study demonstrated a significant decrease in anxiety and depression scores in the intervention group following the Lamaze breathing technique training (p<0.001), and no significant changes in anxiety scores (p = 0.672) and depression scores (p = 0.785) in the control group. It can be concluded that the Lamaze breathing technique is effective in reducing anxiety and depression levels in primiparous mothers.